The Routledge handbook of religion, politics and ideology - Haynes, Jeffrey (Routledge international handbooks, 2022)
"This comprehensive handbook examines relationships between religion, politics and ideology, with a focus on several world religions - Christianity, Islam, Buddhism, Hinduism and Judaism - in a variety of contexts, regions and countries. Relationships between religion, politics and ideology help mould people's attitudes about the way that political systems, both domestically and internationally, are organised and operate. While conceptually separate, religion, politics and ideology often become intertwined and as a result their relationships evolve over time. This volume brings together a number of expert contributors who explore a wide range of topical and controversial issues, including gender, nationalism, communism, fascism, populism and Islamism. Such topics inform the overall aim of the handbook: to provide a comprehensive summary of the relationships between religion, politics and ideology, including basic issues and new approaches. This handbook is a major research resource for students, researchers and professionals from various disciplinary backgrounds, including religious studies, political science, international relations, and sociology"--